2016
DOI: 10.1074/jbc.m115.684738
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein Expression in Macrophages Is Critical for Optimal Clearance of Parasitic Helminth Nippostrongylus brasiliensis

Abstract: The plasticity of macrophages is evident in helminthic parasite infections, providing protection from inflammation. Previously we demonstrated that the micronutrient selenium induces a phenotypic switch in macrophage activation from a classically activated (pro-inflammatory; M1/CAM) toward an alternatively activated (anti-inflammatory; M2/AAM) phenotype, where cyclooxygenase (COX)-dependent cyclopentenone prostaglandin J 2 (15d-PGJ 2 ) plays a key role. Here, we hypothesize that dietary selenium modulates macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…Finally, IL-4 stimulation led to approximately a 10-fold increase in the expression of M2 macrophages that was previously shown to be sensitive to indomethacin (Fig. 1E) (17). Macrophages were first gated by their forward and side scatter characteristics followed by CD11b ϩ F480 ϩ cells, which consisted of ϳ98% of the macrophage population, and were further gated on CD206 ϩ and Arg-1 ϩ (supplemental Fig.…”
Section: Il-4 Stimulation Increases the Expression Of Cox-1mentioning
confidence: 60%
See 4 more Smart Citations
“…Finally, IL-4 stimulation led to approximately a 10-fold increase in the expression of M2 macrophages that was previously shown to be sensitive to indomethacin (Fig. 1E) (17). Macrophages were first gated by their forward and side scatter characteristics followed by CD11b ϩ F480 ϩ cells, which consisted of ϳ98% of the macrophage population, and were further gated on CD206 ϩ and Arg-1 ϩ (supplemental Fig.…”
Section: Il-4 Stimulation Increases the Expression Of Cox-1mentioning
confidence: 60%
“…To extend the analysis of mTORC signaling and Cox-1 in macrophages, we showed that the production of 15d-PGJ 2 was significantly increased with IL-4 stimulation, which was inhibited upon loss of Cox-1 expression by torin 1 as well as metformin. Our data suggested that Cox-1 functionally couples with H-PGDS to likely provide the ligand (15d-PGJ 2 ) to PPAR␥, which acts in concert with Stat6 to activate transcription of PPAR␥ target genes to aid in macrophage (M2) polarization (15)(16)(17)45). More importantly, inhibition of mTORC by metformin, which negatively impacted M2 macrophage polarization through decrease in Cox-1 expression, was rescued by exogenous treatment with 15d-PGJ 2 suggesting the importance of Cox-1 activity in macrophage function.…”
Section: Il-4 Up-regulates Cox-1 Expressionmentioning
confidence: 98%
See 3 more Smart Citations